Color preferences in children’s drawings in Taman Kanak-kanak Alquran Ash Shofa - Nursayyidah, Ade; Ekawardhani, Yully Ambarsih (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to see the color preferences chosen by the students in Taman Kanak-kanak Alquran (which will later be called TKQ) Ash Shofa Bandung while drawing. The research uses a descriptive method in the form of document analysis, through observation of data sources. The documents studied are children’s drawings in TKQ Ash Shofa and related literature. Color is included as a visual element in the drawing one of which is children’s drawing. In this case, color plays a role in conveying the children’s feelings, such as the use of black color when they’re sad, or yellow color when they’re happy. The result of the study found that the color preferences chosen by the students in TKQ Ash Shofa while drawing were the colors that appeared with the highest percentage in children’s drawings. The colors with the highest percentage were red, followed by yellow, light blue, and pink which are light colors. Based on the light colors chosen by the students of TKQ Ash Shofa can be concluded that student’s feelings while drawing are happy, attractive, and pure.